The Effect of Service Quality and Product Quality on Customer Loyalty Hypermart Bengkulu City - Mardhiyah Dwi Ilhami; Sarina Fitriani (Penerbit Jurnal Indonesia, 2023)
This research was conducted at a Hypermart in Bengkulu City, the formulation of the problem in this study was: Does Service Quality and Product Quality Affect Customer Loyalty at Hypermart Bengkulu City, and the purpose of this study was to find out whether Service Quality and Product Quality affect Customer Loyalty at Hypermart City Bengkulu, the sample in this study were 85 respondents, data analysis techniques used documentation, observation, and questionnaires. Based on the results of research that has been done about the effect of Service Quality and Product Quality on Customer Loyalty at Hypermarts in Bengkulu City, it can be concluded as follows: Service Quality has a significant effect on Customer Loyalty at Hypermart in Bengkulu City Product Quality has a significant effect on Customer Loyalty at Hypermart in Bengkulu City, Service Quality (X1) and Product Quality (X2) together have a significant effect on Customer Loyalty (Y) at Hypermart in Bengkulu City. Based on the correlation coefficient test, the value of R = 0.723 and the coefficient of determination R^2 = 0.522 means that Service Quality (X1) and Product Quality (X2) contribute 0.522 or 52.2% to Customer Loyalty (Y) at Hypermart in Bengkulu City while the remaining 0.478 or 47.8% is influenced by other variables not included in this study.